A hybrid analytical–numerical model for calculating the maximum elastic force acting on a flow-driven elastic prolate spheroidal particle during its collision with a rigid wall - Hu, Rongxuan; Liu, Yinshui; Ravnik, Jure; Hriberšek, Matjaž; Steinmann, Paul; Cui, Yan (Computational Mechanics, 2022)
The paper proposes a hybrid analytical–numerical model for calculating the maximum elastic force acting on a flow-driven prolate spheroidal particle during its collision with a rigid wall. This model assumes that the maximum elastic force is a function of normal impact velocity, particle material properties, particle size, particle aspect ratio and particle orientation angle. The relationship between the parameters is determined by dimensional analysis. The remaining unknown coefficients are calibrated by performing finite element (FE) simulations. The solutions for particle aspect ratios of 1.5, 2 and 3 are presented. The proposed model is verified by comparison with independent FE simulation results for different normal impact velocities, particle material properties, particle sizes, particle aspect ratios and particle orientation angles. The results of the comparison between the results of the proposed model and the FE simulation results show a good agreement for small deformations of the particle. The model is valid for any properties of particle material, particle sizes and particle orientation angles.
CRIS-Team Scopus Importer:2022-01-28
Keywords: Elastic force; Finite element simulation; Hybrid analytical–numerical model; Non-spherical particle–wall collision; Prolate spheroidal particle